Effects of Dietary Fats or Oils Supplementations on Fatty Acid Composition of Yolk of Brown Eggs - Sefa Parlat, Sinan; Baris Citil, Ozcan; Yildirim, Iskender (Asian Journal of Chemistry, 2010)
In this study, 140 ATAK-S brown egg layers were used. They were divided into 7 groups, each including 20 hens. The diets of the groups were 3 % soybean oil, sunflower oil, corn oil, palm oil, sufflower oil, sheep's tallow fat and sheep's fail fat, respectively. The fatty acid compositions of brown egg yolk were determined using gas chromatography. Twenty seven different fatty acids were determinated in the compositions of brown egg yolk. At the end of experiment, while the lowest total polyunsaturated fatty acid (PUFA) level was found in sunflower oil group's egg yolk, the highest level was found in sheep's tail fat groups. It was shown that the fatty acid profile played an important role on fatty acid composition of egg yolks. Supplemental soybean oil increased the concentration of ω-3 of egg yolk (2.14 %).